RELEVANSI PERATURAN DAERAH DALAM PEROMBAKAN SATUAN KERJA PERANGKAT DAERAH TERHADAP KINERJA PEMERINTAH PROVINSI DKI JAKARTA - Bima Saputra (2023)
DKI Jakarta as the capital city has become the center of civilization in Indonesia. Therefore, Jakarta should require a well-organized systematic government. Government on a regional scale is managed through Regional Work Units. The plan to reshuffle the SKPD has indeed surfaced since 2019, where it has been about 2 years since Mr. Anies Rasyid Baswedan was inaugurated as Governor of DKI Jakarta. At that time the Governor of DKI Jakarta conveyed the plan to reshuffle the SKPD in a plenary meeting with the DKI Jakarta DPRD, the Governor said that he would reshuffle the existing 42 SKPD, the details of which were that 1 device would be split into 2, then 1 device would be dissolved, and there were 5 devices that would undergo nomenclature changes. However, in its implementation, it needs to be studied in depth whether the reshuffle of SKPD carried out by the DKI Jakarta Provincial Government has run optimally or not, so that it affects the performance of the DKI Jakarta Provincial Government itself. Then, how should the SKPD reshuffle mechanism be in accordance with applicable laws and regulations in Indonesia. This research uses a qualitative method with an analytical descriptive approach. The results showed that the urgency of local regulations in the reshuffle of regional work units on the performance of the DKI Jakarta Provincial Government is very important. With the existence of clear and firm regional regulations, the reshuffle of the work unit role is very important